Studying marriage migration to Europe from below: informal practices of government, border struggles and multiple entanglements. Issue 6 (3rd June 2019) - Scheel, Stephan; Gutekunst, Miriam
Abstract: The growing importance of marriage as a migration strategy has been accompanied by a problematisation and securitization of marriages between binational couples in media and policy discourse. Moreover, marriage migration has received increased scholarly attention. In this article, we propose an analytical framework for the study of marriage migration and its government that permits to transcend three biases and related blind spots that we identify in the existing literature. While this literature offers rich insights into marriage migration and states' ever more laboured attempts to control and regulate it, this literature is, nevertheless, characterised by an implementation gap bias, a control bias and, finally, a destination country bias. To address these biases, we propose an analytical framework that is inspired by the autonomy of migration approach. We propose to ethnographically study binational couples' encounters with marriage migration related authorities in countries of destination and citizenship with a particular focus on binational couples' struggles for visas, resident permits and a right to family life. Illustrated through ethnographic research, we show that this methodology permits to highlight three aspects of marriage migration that have not been sufficiently considered so far. These include the securitization of marriage migration 'from below' through informal practices of government on the 'street-level', binational couples' inherently political border struggles and their capacity to negotiate restrictive legislations and bureaucratic hurdles and, finally, what we call the multiple entanglements of binational couples in the border and citizenship regimes of two or more nation-state orders.